2021
DOI: 10.1002/cam4.4236
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of programmed cell death‐ligand 1 expression on circulating tumor cells in various cancers: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
(145 reference statements)
1
12
0
Order By: Relevance
“…Other studies have shown that PD-L1+ CTCs are associated with poor prognosis in NSCLC ( 39 , 43 - 45 ) and that PD-L1 expression increased at progression ( 46 ). However, in patients receiving immunotherapy, PD-L1 expression by CTC predicted better response to therapy ( 47 , 48 ). Furthermore, we have previously seen that CTCs are associated with abnormalities in peripheral blood immune cells ( 49 , 50 ) suggesting that further study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that PD-L1+ CTCs are associated with poor prognosis in NSCLC ( 39 , 43 - 45 ) and that PD-L1 expression increased at progression ( 46 ). However, in patients receiving immunotherapy, PD-L1 expression by CTC predicted better response to therapy ( 47 , 48 ). Furthermore, we have previously seen that CTCs are associated with abnormalities in peripheral blood immune cells ( 49 , 50 ) suggesting that further study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…On two occasions, the presence of PD-L1 + CTCs was associated with longer PFS and/or OS [ 34 , 41 ]. In a recent meta-analysis, the existence of PD-L1 + CTCs was not associated with PFS or OS; however, in ICI-treated patients, the presence of PD-L1 + CTCs predicted better survival compared to patients undergoing other therapies [ 44 ]. In our study, the presence of PD-L1 and, more specifically, the phenotype CK + PD-L1 + CD45 − at baseline and after one cycle of treatment demonstrated a trend towards lower PFS 12m (log-rank p = 0.073 and log-rank p = 0.094, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, this conclusion requires prospective studies to evaluate the predictive value of PD-L1 expression in ES-SCLC immunotherapy. Circulating tumour cells (CTCs) are a “liquid biopsy specimen” that can replace the primary tumour ( 41 ). The expression of PD-L1 in CTCs can be used to evaluate the efficacy of PD-1/PD-L1 mAbs in non-small cell lung cancer patients ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%